2022
DOI: 10.3390/e24050699
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Dimension Analysis of Earth Magnetic Field during 26 August 2018 Geomagnetic Storm

Abstract: We analyse the fractal nature of geomagnetic field northward and eastward horizontal components with 1 min resolution measured by the four stations Belsk, Hel, Sodankylä and Hornsund during the period of 22 August–1 September, when the 26 August 2018 geomagnetic storm appeared. To reveal and to quantitatively describe the fractal scaling of the considered data, three selected methods, structure function scaling, Higuchi, and detrended fluctuation analysis are applied. The obtained results show temporal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…In general, this result coincided with the results of the papers mentioned in the introduction. It should be noted that, in our calculations, a statistically reliable relationship of HFD with the space weather characteristics was revealed for all components of the geomagnetic field (H, D, Z), while in previous studies [6][7][8][9], a significant decrease in HFD with geomagnetic disturbances was noted only for the horizontal component.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…In general, this result coincided with the results of the papers mentioned in the introduction. It should be noted that, in our calculations, a statistically reliable relationship of HFD with the space weather characteristics was revealed for all components of the geomagnetic field (H, D, Z), while in previous studies [6][7][8][9], a significant decrease in HFD with geomagnetic disturbances was noted only for the horizontal component.…”
Section: Resultssupporting
confidence: 57%
“…The experience of using various methods for estimating the fractal dimension time series has shown that the Higuchi method is one of the most robust methods [9,15]. In this method, the mean distance between the elements of the time series X(j), j = 1, .…”
Section: Higuchi Methods Of Fractal Dimension Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, emergent behaviors may be described by power laws that reflect the distribution of these events across different scales or levels of the system [34][35][36][37]. In physical terms, the power laws that characterize complex systems are closely related to entropy production through the concept of scaling [38][39][40][41][42][43][44]. This is relevant because systems that can be described by power laws lack a characteristic scale, which implies that each component of the system contributes equally to the global evolution of the system, regardless of its scale [45].…”
Section: Introductionmentioning
confidence: 99%